Efektivitas Badan Usaha Milik Nagari dalam Meningkatkan Pendapatan Asli Nagari Padang Laweh Kecamatan Sungai Tarab - Putri, Adinda Mutiara; Lanin, Dasman (YASIN, 2025)
Pendapatan Asli Nagari (PAN), or Village-Generated Revenue, is a crucial indicator in promoting development and economic self-sufficiency at the village level, including in Nagari Padang Laweh, Sungai Tarab Subdistrict. The Badan Usaha Milik Nagari (BUMNag), or Village-Owned Enterprises, plays a strategic role in enhancing PAN through the management of productive, locally oriented business units. This study aims to analyze the effectiveness of BUMNag Padang Laweh in increasing PAN by examining performance achievements, management integration, and adaptive strategies. A qualitative descriptive method was employed, with data collected through interviews, observation, and documentation over the period 2022–2024. The findings indicate that BUMNag management is effective, as evidenced by the cattle fattening business unit contributing an average of 70% of the PAN target, the implementation of financial transparency, and flexible fund management. Management integration operates optimally through synergy among village policies, government capital support, and active community participation in deliberation and oversight. Adaptive strategies, such as annual evaluations, business diversification, and budget efficiency, have enabled BUMNag to maintain its contribution to PAN despite challenges related to limited capital, human resources, and market dynamics. This study underscores the central role of BUMNag as a driver of the local economy capable of sustainably increasing village revenue.